2021
DOI: 10.1136/bmjopen-2020-046357
|View full text |Cite
|
Sign up to set email alerts
|

How to increase the attractiveness of undergraduate rural clerkships? A cross-sectional study among medical students at two German medical schools

Abstract: ObjectivesWhile literature provides substantial evidence that undergraduate rural clerkships may contribute to attract medical students to rural careers, so far little is known about how to convince medical students to choose rural teaching sites for their clerkships, which is usually optional. Thus, this study aimed to investigate students’ preferences and perceptions regarding different rural teaching and clerkship formats, important side conditions and suitable communication strategies to promote rural cler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These ideas are supported by data from another project hosted by our faculty that involved fostering clerkships in rural areas. Herget et al found out that ‘financial and organisational issues including remuneration of the clerkship, cost absorption for travelling and accommodation, and accessibility by public transport were the most important side conditions to increase the attractiveness of rural clerkships’ 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ideas are supported by data from another project hosted by our faculty that involved fostering clerkships in rural areas. Herget et al found out that ‘financial and organisational issues including remuneration of the clerkship, cost absorption for travelling and accommodation, and accessibility by public transport were the most important side conditions to increase the attractiveness of rural clerkships’ 28…”
Section: Discussionmentioning
confidence: 99%
“…Herget et al found out that 'financial and organisational issues including remuneration of the clerkship, cost absorption for travelling and accommodation, and accessibility by public transport were the most important side conditions to increase the attractiveness of rural clerkships'. 28 The mentor There is substantial knowledge on student-preceptor relationships in general and, more precisely in this context, the benefit of mentoring for medical students. [29][30][31] Brought to the point by Schultz et al, students taught in community settings value 'feedback by enthusiastic, open preceptors who are willing to discuss their reasoning processes and delegate responsibility'.…”
Section: Structural Reasonsmentioning
confidence: 99%
“…[Table12.] International comparison of the attractiveness of rural career[78][79][80][81][82][83][84]…”
mentioning
confidence: 99%